2011
DOI: 10.4061/2011/983869
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Practice of PHC Physicians toward the Detection and Management of Hypertension and Other CVD Risk Factors in Egypt

Abstract: Aim. To assess the knowledge and practice of PHC physicians toward the detection and management of hypertension (HTN) and other CVD risk factors. Methods. A cross-sectional study of all primary health care physicians of the FHU of three rural districts of Egypt was conducted. Each physician was subjected to a prevalidated interview questionnaire on the WHO-CVD risk management package for low and medium resources, and a checklist of observation of daily practices. Results. Hypertension was a priority problem in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 16 publications
1
9
1
Order By: Relevance
“…This clearly indicates that there is a lack of transfer of knowledge by physicians to patients. The role of physicians has already been appraised in previous studies [25]. Our study results showed no association between controlled BP status and hypertension knowledge, in contrast with previous studies that showed an association between hypertension knowledge and compliance with treatment in hypertensive patients [4].…”
Section: Discussioncontrasting
confidence: 90%
“…This clearly indicates that there is a lack of transfer of knowledge by physicians to patients. The role of physicians has already been appraised in previous studies [25]. Our study results showed no association between controlled BP status and hypertension knowledge, in contrast with previous studies that showed an association between hypertension knowledge and compliance with treatment in hypertensive patients [4].…”
Section: Discussioncontrasting
confidence: 90%
“…Also this result is consistent with the results of the study conducted by Abolfotouh, [32] who found that experience was not significantly associated with the level of knowledge. This might reflect the necessity of continuing medical education programs for all physicians irrespective of their previous experience.…”
Section: Ii-characteristics Of Studied Family Physicianssupporting
confidence: 92%
“…This clearly indicates that apart from lack of appropriate health education, there seems to be a lack of transfer of knowledge by physicians to patients and requires exploration. Role of physicians has been critiqued in several studies in terms of lack of knowledge and practice of treating hypertension [30-32]. We found that factors associated with knowledge scores were male gender, having uncontrolled hypertension and ethnicity.…”
Section: Discussionmentioning
confidence: 78%